The Influence Of Leadership Style, Organizational Culture And Organizational Commitment On Employee Performance In Regional Government Offices Of Bengkulu Province - Gagasadewa, Putra; Gayatri, Ida Ayu Made Er Meytha; Nurzam, Nurzam (Journal of Management, Economic, and Accounting, 2025)
The purpose of this study is to determine the effect of Leadership Style, Organizational Culture, and Organizational Commitment on the performance of employees of the Bengkulu Provincial Government Office. The type of research is quantitative, the sample in this study was 50 Bengkulu Provincial Government Office Employees. Data collection using Questionnaires and the analysis methods used are multiple linear regression, determination test and hypothesis test.The results of the study indicate that the Leadership Style variable (X1) shows a t count of 2.942> t table 1.677 and significant 0.005 <0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Leadership Style (X1) has a positive and significant effect on Performance (Y). The Organizational Culture variable (X2) shows a t count of 3.656> t table 1.677 and significant 0.001> 0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Organizational Culture (X2) has a positive and significant effect on Performance (Y). The Organizational Commitment variable (X3) shows a t count of 3.079> t table 1.677 and significant 0.003 <0.05, then the results of the Ha hypothesis are accepted and Ho is rejected, meaning that Organizational Commitment (X3) has a positive and significant effect on Performance (Y). Based on the results of simultaneous hypothesis calculations, it shows a significant value of 0.000 < 0.05, meaning that together the variables X1 Leadership Style, X2 Organizational Culture, X3 Organizational Commitment have a positive and significant influence on Performance (Y).